Kearifan Lokal, Adat, Dan Politik: Relasi Pemerintah Desa Dengan Kasepuhan Guradog - Hilda Fitriyanti; Habibi Maulana; Nadia Khumairatun Nisa; Ivana Joya Mahadina; Kheysa Husna (Sociale : Journal of Social and Political Sciences, 2026)
This study examines the relationship between the village government and the customary institution in Kasepuhan Guradog, Lebak Regency, Banten Province, emphasizing the role of Abah Olot as a traditional leader who holds significant influence over local socio-political structures. The purpose of this study is to understand how customary authority interacts with formal power to create a balanced governance system. The research applies a qualitative approach using the phenomenological method as described by Creswell (2014), through in-depth interviews, observation, and documentation involving traditional leaders and village officials. The results show that the relationship between the village head and Abah Olot is complementary and symbiotic, where customary approval provides social legitimacy for government policies, strengthening social cohesion, and administrative effectiveness. Moreover, regular deliberation forums between the village government and the customary community encourage the creation of policies that align with local values. However, the study also identifies potential kinship-based dominance since the village head is a descendant of Abah Olot, which may lead to a patronage system that limits broader public participation. The emergence of multiple candidates in recent village elections indicates a gradual shift toward a more democratic process. This study concludes that the governance system in Kasepuhan Guradog represents a hybrid form of power, a negotiated balance between the state and customary authority, demonstrating the adaptability of indigenous communities to modernization while preserving their cultural identity.